Controlled Release of Flavor Substances from Sesame-Oil-Based Oleogels Prepared Using Biological Waxes or Monoglycerides - Min Pang; Lulu Cao; Shengmei Kang; Shaotong Jiang; Lili Cao (Foods, 2021)
The flavor substances in sesame oil (SO) are volatile and unstable, which causes a decrease in the flavor characteristics and quality of SO during storage. In this study, the effect of gelation on the release of flavor substances in SO was investigated by preparing biological waxes and monoglycerides oleogels. The results showed that the release of flavor substances in SO in an open environment is in accordance with the Weibull equation kinetics. The oleogels were found to retard the release of volatiles with high saturated vapor pressures and low hydrophobic constants in SO. The release rate constant k value of 2-methylpyazine in BW oleogel is 0.0022, showing the best retention effect. In contrast, the addition of gelling agents had no significant retention effect on the release of volatiles with low saturated vapor pressures or high hydrophobic constants in SO, and even promoted the release of these compounds to some extent. This may be due to the hydrophilic structural domains formed by the self-assembly of gelling agents, which reduces the hydrophobicity of SO. This work provides a novel approach for retaining volatile compounds in flavored vegetable oils. As a new type of flavor delivery system, oleogels can realize the controlled release of volatile compounds.